Balance Testing Following Concussion: Postural Sway versus Complexity Index. Issue 11 (3rd April 2019) - Purkayastha, Sushmita; Adair, Heather; Woodruff, Amanda; Ryan, Laurence J.; Williams, Benjamin; James, Eric; Bell, Kathleen R.
Abstract : Background: Although postural control deficits are common following a concussion, the current clinical assessments for postural control tend to resolve within 3 to 10 days after injury. There is a lack of sensitive tools to examine subtle changes in postural control during the recovery phase following sports‐related concussion. Only a limited number of studies have examined nonlinear dynamics of postural control; no study has examined this metric longitudinally during the recovery phase following a sports‐related concussion. Objective: To examine sway and complexity index of postural control in collegiate athletes during day 3, day 21, and day 90 following a concussion and compare them with noninjured controls. Design: Prospective longitudinal case‐control study. Setting: University cerebrovascular research laboratory. Participants: Thirty‐one male and female collegiate athletes on day 3 following a concussion. Twenty‐eight athletes returned on day 21, and 21 completed assessments on day 90. Twenty‐nine sports‐matched noninjured controls. Methods: Center of pressure (COP) measurements obtained during 60‐second quiet standing on a force plate system with either eyes opened or closed. Postural sway was estimated as range and variability of COP in the anteroposterior (AP) and mediolateral planes. Main Outcome Measurements: Complexity index of AP COP utilizing multiscale entropy analysis. Results: Postural sway measured as AP range ( P = .03) and variability ( P = .04) during quiet standing with eyes closed were higher on day 3 compared to the controls. Postural sway in the concussed group was comparable to the noninjured controls by day 21 postinjury. However, postural control dynamics utilizing complexity index was lower on day 3 ( P < .001) and persisted on day 21 ( P < .006) and day 90 ( P < .02), despite resolution of abnormal postural sway 21 days postinjury. Conclusion: Complexity index utilizing nonlinear dynamics might be a more sensitive objective biomarker for examining postural control following a concussion, with implications for return‐to‐play and interventions. Future studies with a larger sample size are needed to validate this finding. Clinical Trial Number: NCT02754206. Level of Evidence: III.